2018
DOI: 10.1093/brain/awx382
|View full text |Cite
|
Sign up to set email alerts
|

Migraine with visual aura associated with thicker visual cortex

Abstract: Until recent years it was believed that migraine with aura was a disorder causing intermittent neurological symptoms, with no impact on brain structure. However, recent MRI studies have reported increased cortical thickness of visual and somatosensory areas in patients with migraine with aura, suggesting that such structural alterations were either due to increased neuronal density in the areas involved, or a result of multiple episodes of cortical spreading depression as part of aura attacks. Subsequent studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 34 publications
6
65
0
Order By: Relevance
“…In contrast, a study with MwA found cortical thickness increases which were most pronounced in V5 and V3A. 34 In addition, a recent study revealed increased cortical thickness in V2 and V3A in females with MwA compared to controls, and increased cortical thickness of V2 in twins with MwA compared to their discordant twin pairs, 53 indicating that structural changes in visual cortex may be an inherent trait. Whether this is true for functional brain alterations needs to be addressed in future studies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, a study with MwA found cortical thickness increases which were most pronounced in V5 and V3A. 34 In addition, a recent study revealed increased cortical thickness in V2 and V3A in females with MwA compared to controls, and increased cortical thickness of V2 in twins with MwA compared to their discordant twin pairs, 53 indicating that structural changes in visual cortex may be an inherent trait. Whether this is true for functional brain alterations needs to be addressed in future studies.…”
Section: Discussionmentioning
confidence: 96%
“…34 In addition, a recent study revealed increased cortical thickness in V2 and V3A in females with MwA compared to controls, and increased cortical thickness of V2 in twins with MwA compared to their discordant twin pairs, 53 indicating that structural changes in visual cortex may be an inherent trait. We did not find increased cortical thickness or volume in the clusters with increased CBF, except of a larger volume in the right STG (P < .001, uncorrected).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with HC, patients with MwA (eg, both concordant and discordant twin pairs) showed a thicker V2 and V3A cortex, while MwA discordant twin pairs (eg, patients with a co‐twin without MwA) only differed in V2 thickness. Taken together, the authors suggested that slightly thicker cortical visual areas observed in patients with MwA are more likely to represent a trait correlating with this type of migraine rather than a result of aura attacks …”
Section: Functional Neuroimaging Investigationsmentioning
confidence: 90%
“…Increased thickness of V2 and V3A areas was confirmed in a large cohort of female patients with exclusively MwA . More specifically, Hougaard and colleagues conducted a cross‐sectional study, recruiting from the nationwide Danish Twin Registry, 166 female patients with MwA, 30 co‐twins controls without MwA, and 137 HC . The authors performed an “individual‐based analysis” between twin subjects without migraine and twin patients experiencing MwA (only a little percentage was suffering also from MwoA).…”
Section: Functional Neuroimaging Investigationsmentioning
confidence: 99%
See 1 more Smart Citation